Imaging of trabecular meshwork using Bessel–Gauss light sheet with fluorescence. (26th January 2017) - Hong, Xun Jie Jeesmond; Shinoj, V K; Murukeshan, V M; Baskaran, M; Aung, Tin
Abstract: Ocular imaging technology that holds promise for both fundamental investigation and clinical detection of glaucoma is still a challenging research area. A direct view of the trabecular meshwork (TM) with high resolution is not generally possible because the iridocorneal angle region is obstructed by the sclera overlap. The best approach to observe the aqueous outflow system (AOS) is therefore to view from the opposite angle. In this research work, we developed two imaging systems for the high resolution ex vivo studies of the AOS inside porcine eye, based on a Gaussian illuminated and a digitally scanned Bessel–Gauss beam light sheet fluorescence configurations. The digitally scanned Bessel–Gauss beam is able to overcome the trade-off between the length and thickness of the Gaussian light sheet to give better imaging performance. It has adequate spatial resolution to resolve critical anatomical structures such as the TM, thereby enabling objective information about the AOS. This non-contact and non-invasive imaging methodology with excellent safety profile is expected to be well received by vision researchers and clinicians in the evaluation and management of glaucoma.